The investigation on ionic conduction of PEMA based solid polymer electrolytes - Amir, S.; Mohamed, N.S.; Yahaya Subban, R.H. (2009)
Solid polymer electrolytes comprising of various weight ratios of poly(ethyl methacrylate) (PEMA) and lithium perchlorate (LiCl04) salt were prepared via solution casting technique using N,N-Dimethylformamide (DMF) as the solvent. The conductivity values of the electrolytes were determined utilizing Solatron 1260. The highest conductivity obtained is in the order of 10-6 S ern -I. Structural properties of the electrolytes were investigated by X-ray diffraction and the results show that the highest conducting film is the most amorphous.